Neuroprotective effect of L-kynurenine sulfate administered before focal cerebral ischemia in mice and global cerebral ischemia in gerbils - Gigler Gábor (EUROPEAN JOURNAL OF PHARMACOLOGY, 2007)
Excessive stimulation of N-methyl-D-aspartate (NMDA) receptors during ischemia contributes to apoptotic and excitotoxic nerve cell death. Kynurenic acid is a selective antagonist at the glycine co-agonist site of the NMDA receptor complex at low concentration, and it is a broad-spectrum excitatory amino acid receptor blocker at high concentration. Kynurenic acid provides neuroprotection in animal models of cerebral ischemia only at very high doses as it hardly crosses the blood-brain barrier. The neuroprotective effect of L-kynurenine sulfate, a precursor of kynurenic acid, was therefore studied because L-kynurenine readily crosses the blood-brain barrier. L-kynurenine sulfate was administered 15 min before permanent focal cerebral ischemia produced by electrocoagulation of the distal middle cerebral artery in mice. L-kynurenine sulfate induced a small decrease in the surface area of the brain infarction (10%, P<0.05) at 30 mg/kg i.p., and it caused strong reductions in infarct size (24-25%, P<0.01) at 100 and 300 mg/kg i.p. Treatment of gerbils with L-kynurenine sulfate at 300 mg/kg i.p. 2 h before a 3-min bilateral carotid occlusion decreased (40%, P<0.01) the pyramidal cell loss in the CAl area of the hippocampus. Furthermore, L-kynurenine sulfate inhibited the ischemia-induced hypermotility (77%, P<0.001), and decreased (50%, P<0.01) the ischemia-induced deterioration of spontaneous alternation, a measure of spatial memory, without altering the rectal temperature. In conclusion, the administration of L-kynurenine can elevate the brain concentration of kynurenic acid to neuroprotective levels, suggesting the potential clinical usefulness of L-kynurenine for the prevention of neuronal loss. (c) 2007 Elsevier B.V. All rights reserved.